Urban and Military Defense in Ancient Rome: Infrastructure, Strategy, and Capital Security (International Journal of World Civilizations and Philosophical Studies, 2026)
This study examines the military defense system of ancient Rome, focusing on how its cities and military infrastructure evolved from the founding of the Roman Empire in 27 BCE to 284 CE. It highlights the technological innovations and strategic decisions that allowed Rome to maintain imperial dominance. Using historical analysis of significant architectural structures such as the Aurelian Walls, along with the layout of key military sites including barracks and ports in the capital, the research explores how Rome organized its defenses. It also investigates the role of the Tiber River, its bridges, canals, and surrounding facilities in supporting both military operations and economic activities. The study emphasizes the importance of critical military infrastructure, including warehouses, ports, and the extensive road network, which sustained Rome’s economy and defense. The findings show that Rome’s integrated system of garrisons, fortified structures, and natural features effectively countered external threats and preserved internal security. Key roads, exemplified by the Appian Way, facilitated the rapid movement of troops and supplies, thereby strengthening stability across the empire. Overall, the research demonstrates how Rome’s advanced coordination of defense, logistics, and urban planning contributed significantly to the resilience and longevity of the Roman Empire.